The ICJ Advisory Opinions in the Mechanism of Ensuring of Meeting Commitments under International Treaties - Natalia S. Simonova (Московский журнал международного права, 2015)
An article deals with significance of advisory opinions of the International court of justice for the process of ensuring for meeting commitments under international treaties. This article stressed upon the problem of entities that empowered to bring judicial questions before the Court as well as the problem of advisory opinions’ nature. Being based on analysis of the ICJ advisory practice the main conclusion concerning the res judicata essence of the ICJ advisory opinions is done. Advisory opinions’ usage for meeting commitments under international treaties is underlined.